Debundling accountability: prosecutor and public defender elections in Florida. (1st October 2021) - McCannon, Bryan C.
Abstract : I explore the impact of public defender and prosecutor elections using caseload data from Florida. While most states within the US use popular elections to select and retain prosecutors, public defenders are typically appointed positions. Florida is novel in that for both positions, popular, partisan elections are used to select the office's leader. I first document important distortions in pre-trial case handling. A public defender re-election is associated with an increase in the proportion of cases resolved via plea bargaining, while prosecutor re-elections are associated with less plea bargaining. At the trial phase, I present evidence that public defender re-elections are associated with a decrease in the proportion of jury trials that result in a conviction, while a prosecutor re-election coincides with an increase in the conviction rate. The results are consistent with voters holding both elected officials accountable for doing their job. Public defenders obtain plea bargains at a higher rate and secure acquittals for their clients when up for re-election. Prosecutors do not plea bargain as much and win at trial when up for re-election.